Squalene Supplementation as a Novel to Increase PUFA Content in Fish Tissues - Piotr Niewiadomski; Piotr Gomułka; Małgorzata Woźniak; Mariusz Szmyt; Elżbieta Ziomek; Helena Bober; Mirosław Szczepkowski; Katarzyna Palińska-Żarska; Sławomir Krejszeff; Daniel Żarski (Animals, 2023)
Squalene is an antioxidant that plays an essential role in fat metabolism. The study aimed to assess the effect of squalene supplied in feed on the growth performance, health status, and fatty acid profiles of muscle and liver of Siberian sturgeon, rainbow trout, and Eurasian perch. The experimental feeds containing 0%, 0.5%, and 1.0% squalene were prepared for each fish species. Hematological and biochemical indices, liver histology, and fatty acid profiling of muscle and liver were analyzed. Squalene supplementation was safe for fish, and no negative influence on growth status was observed. However, changes in the values of hematological and biochemical indicators were found, including the level of triglycerides in the blood of rainbow trout, and cholesterol in the blood of Eurasian perch. The addition of squalene influences the nucleocytoplasmic index values in all fish offered feed containing 1% squalene. The retention of squalene in the liver and muscle of experimental Siberian sturgeon was observed in both 0.5% and 1.0% squalene levels of feed. The PUFA and docosahexaenoic acid increase was observed in all fish in groups with squalene addition. Dietary squalene increases the content of PUFAs in tissues of the examined species.